A contribution to the bionomics and control of the mite Bryobia praetiosa Koch, (Fam. Tetranychidae) - Georgala, M. B (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1954.